The Effect of Social Media Content and Personal Background Performance on Financial Planning Awareness of Generation Z Muslim - Muhammad Raihan Gunawan; Mutya Qurratu’ayuni Mustafa; Nisrina Zalfa Salsabil (SMART Insight, 2020)
Social media contents on Islamic financial planning are spreading out massively. However, the study on how it impacts the awareness of Muslims society in financial planning is still rarely found. The aim of this study is to examine the impact of Islamic financial planning social media content towards the awareness of financial planning among generation Z Muslims. In addition, personal background variable is also included in the analysis. One hundred sixty-five generation Z Muslims became the participants of this research. They filled the questionnaire regarding their perspectives on social media content’s impact on their knowledge of personal financial planning. This study hypothesized that social media content and personal background both affecting generation Z Muslims on their understanding about Islamic financial planning. By using multi linear regression analysis, the study revealed that the result is quite favorable. The study shows that 68% of Instagram social media content have affected the awareness of Islamic financial planning among generation Z Muslims, while the 22% came from personal background. Future research in the area is needed for a more complete understanding on how social media content affects the behavior of young Muslims in terms of financial planning for a better Islamic financial inclusion.